A 3-month period of electronic monitoring can provide important information to the healthcare team to assess adherence and improve asthma control. Issue 3 (26th July 2021) - Jochmann, Anja; Artusio, Luca; Usemann, Jakob; Jamalzadeh, Angela; Bush, Andrew; Frey, Urs; Fleming, Louise J.
Poor adherence to inhaled corticosteroids (ICS) results in poor asthma control, asthma attacks and increased healthcare costs [1, 2]. Measuring adherence using electronic monitoring devices is more accurate than self-report, prescription refill data or canister weight [3–5]. In children with difficult asthma, a single period of electronic monitoring can help to assess a patient's adherence and the possible impact of improved adherence on asthma control https://bit.ly/3c3Gj6n